2009
DOI: 10.1128/aac.00638-09
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activities of Piperaquine, Lumefantrine, and Dihydroartemisinin in Kenyan Plasmodium falciparum Isolates and Polymorphisms in p fcrt and p fmdr1

Abstract: We have analyzed the in vitro chemosensitivity profiles of 115 Kenyan isolates for chloroquine (CQ), piperaquine, lumefantrine (LM), and dihydroartemisinin in association with polymorphisms in pfcrt at codon 76 and pfmdr1 at codon 86, as well as with variations of the copy number of pfmdr1. The median drug concentrations that inhibit 50% of parasite growth (IC 50 s) were 41 nM (interquartile range [IQR], 18 to 73 nM), 50 nM (IQR, 29 to 96 nM), 32 nM (IQR, 17 to 46 nM), and 2 nM (IQR, 1 to 3 nM) for CQ, LM, pip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

32
156
6

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(194 citation statements)
references
References 43 publications
32
156
6
Order By: Relevance
“…The YYD haplotype significantly increased in 2014, in contrast to Kenya and Tanzania where a decrease of Lumefantrine susceptibility was reported followed by increase of the prevalence of NFD, NYD, YYY and YYD [44,36]. A rise of YYD in 2014 was observed and is consistent with the work of Morris U et al who reported that YYD is the most prevalent haplotype in asymptomatic malaria infection [45].…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…The YYD haplotype significantly increased in 2014, in contrast to Kenya and Tanzania where a decrease of Lumefantrine susceptibility was reported followed by increase of the prevalence of NFD, NYD, YYY and YYD [44,36]. A rise of YYD in 2014 was observed and is consistent with the work of Morris U et al who reported that YYD is the most prevalent haplotype in asymptomatic malaria infection [45].…”
Section: Discussionsupporting
confidence: 81%
“…A relative high prevalence of mutant types 184F and 1246Y in samples from 2013 (54.76 and 64.0%, respectively) was [39,36].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This result reveals a pleiotropic role for this recently emerged pfcrt allele in modulating parasite susceptibility to clinically important antimalarials. This role differs from what is generally observed in Africa with the PfCRT CVIET haplotype or even the PfCRT SVMNT haplotype in Papua New Guinea (29,30). This effect of C350R on QN and MQ, however, was not replicated in field isolates, underscoring a complex genetic basis of susceptibility in the field.…”
Section: Discussioncontrasting
confidence: 45%